Pengaruh Kafein Terhadap Ekspresi RANKL dan Jumlah Osteoklas Pada Pergerakan Gigi Ortodonti - Herniyati (Denta Journal Kedokteran Gigi, 2016)
Background: Orthodontic tooth movement depends on bone remodeling involving osteoclasts and osteoblasts. RANKL has an important role in osteoclastogenesis and increased during orthodontic tooth movement. Caffeine contained in coffee, tea, and carbonated drinks can increase osteoclastogenesis. Purpose: To analyze the effect of caffeine on the expression of RANKL and the number of osteoclasts in orthodontic tooth movement. Materials and Methods: The experimental laboratories research used 16 rats were divided into 2 groups: the control group (K): rats given orthodontic mechanical force (OMF) and the treatment group (P): rats given OMF and caffeine at 1,37mg / 100 g twice a day. OMF was conducted by ligature wires were applied on permanent maxillary right first molar and both permanent maxillary incisivus .Subsequently, the permanent maxillary right first molar moved to mesial with Ni-Ti orthodontic closed coil spring. Observations were made by histological examination to calculate the number of osteoclasts and immunohistochemical examination to determine the expression of RANKL. Result: the administration of caffeine increased the number of osteoclast in both compression and tension areas (p<0.05). The number of osteoclast in compression area larger than those which in tension area (p<0.05), The administration of caffeine improved the expresion of RANKL in both compression and tension areas (p<0.05). The expression of RANKL in compression area larger than those which in tension area (p<0.05), Conclusion: The administration of caffeine increased the expression of RANKL and osteoclast numbers on orthodontic tooth movement, therefore it may be an alternative to accelerate orthodontic treatment.